(untitled) (Bangladesh Journal of Infectious Diseases, 2017)
A 18 years old boy presented with severe diffuse abdominal pain, constipation, abdominal distention, fever and diagnosed as a case of perforation as free gas noted under both dome of the diaphragm. After resuscitation, exploratory laparotomy was done and diagnosed as a case of multiple spontaneous leaky perforations of jejunum and ileum 25 to 30 cm from duodeno-Jejunal flexure (DJ) up to terminal ileum. Peritoneal toileting and excisional biopsy of the mesenteric lymph node were done. Operative and postoperative period were uneventful. Histopathological examination of the resected lymph node revealed granulomatous inflammation compatible with tuberculosis. Anti-tubercular therapy was started and continued for 6 months. Patient was discharged on the 12th postoperative day in a good condition. At 3 months of follow up the patient was asymptomatic and thriving well. Free perforation is one of the most feared complications of the intestinal tuberculosis. The terminal ileum is the most common site of perforation, while the majority of (90%) perforations are solitary. Bangladesh Journal of Infectious Diseases 2016;3(2):52-54